SOCIETY’S WILLINGNESS TO PAY FOR ENVIRONMENTAL FRIENDLY WASTE MANAGEMENT IN DUSUN TOISAPU LANDFILL, AMBON DISTRICT - Angela Ruban; Eka Intan Kumala Intan Kumala Putri; Meti Ekayan (Pusbindiklat - LIPI, 2015)
Waste is a national problem in Indonesia. This is related to the old paradigm of waste management which is only collected, transported, and disposed to the landfill. The same problem occured in Dusun Toisapu, Ambon. Since it’s establishment in 2003, Dusun Toisapu landfill used open dumping and it’s caused the increased negative externalities of environmental quality for the people who lives nearby. Ambon district officer has a new integratedwaste management in 2012 but the implementation is not going well because there was no sorting of waste (organic and anorganic) on source of waste. The governments finacial limitation causes the waste management services not running properly. Based on the results of research in Baguala and Nusaniwe, most people are willing to pay higher retribution for better services in Dusun Toisapu landfill with four scenarios. The highest average WTP in Baguala is Rp24.250,00/family/month for biogas scenario and the lowest is Rp20.804,00/family/month for incineration scenario. In Nusaniwe, it is obtained the highest average WTP is p21.228,00/family/month for composting scenario and the lowest is Rp18.220,00/family/month for sanitary landfill scenario. Value of WTP from people can cover operational costs for implementing four waste management scenarios that offered.